KOMUNIKASI KEBIJAKAN PEMERINTAH MELAHIRKAN PELANGGARAN DALAM KEBAKARAN HUTAN DAN LAHAN - Irsadi Aristora (SOURCE : Jurnal Ilmu Komunikasi, 2016)
A result of the magnitude of the impact of the effects damage to of smoke and nature due to impact of about fire that, Part of institutions in this country wash hands and throw the ball the heat to other institutions. Governmental Organization (NGO), both nationally and abroad accuse the fault is on the part of country that have issued permits in areas that should not be issued. While the institution of ministry mutual self-defense and ministries blame the institution other as an object of the problems responsible for the incident. James A.F. Stoner, and Charles Wankel (1989) argues that the communication is one way humans relate that involves understanding or intention, on the condition that they have to agree with the definition of terms used by something symbolic like signs, letters, numbers, and words that symbolize or resemble ideas that can convey meaning. Then, according to Littlejohn importance of communication is: something everyday casual look, turned into a big puzzle for someone so he wanted to find meaning / understanding hidden inside something that. So, the communication aims to search for meaning. Licensing Service Agency integrated (BP2T) whose job it authorizes the issuance of licenses on the proposerwithout referring to the legislation in force in the country. Government policyCommunication more clearly visible so not running properly In legal terms "stric liability" can be accounted deed to anyone, who has a real basis on legal facts giving Permissions area has been declared a protected area that should be protected by law and regulations. Keywords: Communication Policy, Land and Forest Fire.